SNAPIN Regulates Cell Cycle Progression to Promote Pancreatic β Cell Growth - Jiang, Mengxue; Kuang, Zhijian; He, Yaohui; Cao, Yin; Yu, Tingyan; Cheng, Jidong; Liu, Wen; Wang, Wei (Frontiers in Endocrinology, 2021)
In diabetes mellitus, death of β cell in the pancreas occurs throughout the development of the disease, with loss of insulin production. The maintenance of β cell number is essential to maintaining normoglycemia. SNAPIN has been found to regulate insulin secretion, but whether SNAPIN induces β cell proliferation remains to be elucidated. This study aimed to explore the physiological roles of SNAPIN in β cell proliferation. SNAPIN expression increased with the age of mice and SNAPIN is down-expressed in diabetes. KEGG pathway and GO analysis showed that SNAPIN and its interacting proteins enrich the cell cycle. Β cell cycle was arrested in the S phase after SNAPIN knockdown, and cell proliferation was inhibited after SNAPIN knockdown. The expression of proteins CDK2, CDK4 and CCND1 expression in the S phase of the cell cycle were reduced after SNAPIN knockdown. And the expression of proteins CDK2, CDK4 and CCND1 expression in the S phase of the cell cycle were increased after overexpression of SNAPIN. In addition, insulin protein/mRNA levels also increased or decreased after SNAPIN knockdown or overexpression, respectively. Conclusions: Our data indicate that SNAPIN mediates β cells proliferation and insulin secretion, and supply the evidence for the SNAPIN/analog being a pharmacotherapeutic target for diabetes mellitus.